Prevalência de hiperuricemia e fatores nutricionais associados: um estudo transversal com nipo-brasileiros do município de Bauru - Poletto, Juliana [UNIFESP] (2009)
This study aimed to estimate the prevalence of hiperuricemia among Japanese-Brazilians living in Bauru city (Sao Paulo) as well to verify the existence of associations between this disease and nutritional factors. METHODS: Data were obtained from 1,330 individuals using previously tested questionnaires (demographic, health history and food intake data), physical examination (health status and blood pressure) and laboratory procedures (uric acid, creatinine, fasting and 2 h glucose, total cholesterol and fractions). Chi-square and prevalence ratios were used to evaluate associations between hyperuricemia and nutritional variables. RESULTS: The prevalence of hyperuricemia was 35.3% and it occurred more frequently among smoker individuals, men subjects, aged . 55 years, with overweight or obesity, central obesity, glucose intolerance, hypercholesterolemia, hypertrigliceridemia, using specific drugs and with creatinine levels >1.4 mg/dL. We found in the crude analysis that hiperuricemia was associated with total calories, total fat, saturated, alcohol, red and processed meats, milk and dairy products, and citric fruits intake. After control variables adjustment remained statistically significant the associations between hyperuricemia and body weight excess, central obesity, hypertrigliceridemia and use of specific drugs. CONCLUSION: High hiperuricemia prevalence rate was found among these Japanese-Brazilians and changes in nutritional profile including weight and body fat reductions may help to minimize the occurrence of this disease in that community.